Commentary on Indonesia philanthropy rank - Zainal Abidin; Ani Cahyadi (LPMP Imperium, 2023)
Indonesian philanthropy has experienced substantial turmoil since early 2020. The Doing Good Index 2020 survey raised Indonesia's position to 'Doing Okay' after several years in the 'Not Doing Enough' position. This index includes indicators such as monetary donations, time contributions, and assistance to foreigners. Indonesia often ranks high on the indicators for contributing time and assistance to foreigners in this index. The question that arises from this ranking is whether it has anything to do with Islamic philanthropy? and whether the alleged misappropriation of charitable funds through various social and commercial activities will affect public confidence. This commentary focuses Strictly on the perspective of Islam and Indonesia in general in understanding philanthropy. Public interest statements This brief provides practitioners and academics with information on the development of philanthropy in Indonesia during and after the COVID-19 pandemic and after the revelations of the ACT case. Regardless of trends and rankings, philanthropy helps raise social awareness of the problems and challenges faced by society. Philanthropy involves developing human values such as kindness, empathy, cooperation, and concern for others. Article history Received: 6/1/2023 | Revised: 6/9/2023 | Accepted: 6/11/2023 | Online First: 6/12/2023